Maternal Serum Placental Protein-13 Levels in the Prediction of Pregnancies with Abnormal Invasive Placentation - Şahin, Banuhan; Turhan, Uğur; Şahin, Buğra; Dağ, İsmail; Tinelli, Andrea (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective To evaluate whether placental protein-13 (PP-13) measured in the serum of pregnant women could predict abnormal invasive placentation (AIP) detected by color Doppler ultrasound (US) and magnetic resonance imaging scan in addition to the routine US scan during the third trimester.Materials and methods The prospective case-control study included patients subdivided in 2 groups: 42 pregnant women with a singleton pregnancy at 28–32 weeks of gestation with only suspected AIP, and 32 healthy pregnant women. The serum PP-13 levels were measured in both groups using an enzyme-linked immunosorbent assay (ELISA) method and statistically compared. The cases of AIP were confirmed by placental histopathological examination and/or the uterus removed by hysterectomy after elective caesarean section.Results Serum PP-13 levels of pregnant women with AIP were significantly higher (p<0.001) than those of controls (650.32±387.33 vs. 231.43±94.33). Statistical analysis of maternal serum PP-13 levels above the threshold of 312 pg/ml (measured in the early third trimester) predicted AIP with 76.2% sensitivity and 75% specificity.Conclusion Maternal serum PP-13 may have a role in the pathophysiology of AIP owing to its high serum value in the AIP group. The maternal serum dosage of PP-13 levels could improve pregnancy management in those patients suspected of having AIP.
Keywords: Abnormal invasive placentation; Placenta acreta; Placenta increta; Placenta percreta; Placental protein-13; Pregnancy